Efeitos da escarificação e aração na fertilidade de solo com fragmentos rochosos sob plantio direto - Rodrigues, Seninho Julio (2023)
The soils of Brazil often face challenges related to subsurface acidity due to limited limestone movement at greater depths along the soil profile. This results in deeper soil layers that may contain toxic levels of aluminum, even after proper liming. Therefore, conventional methods used in deep soils involving intensive soil mobilization are known for correcting subsurface acidity in rocky soils, making them susceptible to greater soil losses. In this context, this research was conducted to test different soil management strategies for correcting subsurface acidity and fertility in lowly transformed soils with rocky fragments under no-till systems. Conducted in the Ivorá/RS region, the research aimed to evaluate three soil management systems implemented in 2021, taking into account the principles of soil mobilization and non-mobilization for the application of limestone, phosphorus (P), and potassium (K) in the soil. Surface application with and without incorporation of limestone, P, and K was carried out. The different soil management systems included no-till (SPD), soil scarification (ESC), both with surface application without incorporation of limestone, P, and K, and the third soil management system with scarification and surface application of limestone, P, and K, followed by incorporation with a smooth disc plow (ESC+AR). Stratified soil samples were collected at a depth of 0-50 cm, 18 months after the application of limestone, P, and K, for chemical analysis of acidity and fertility parameters. Stratified maize root samples were also collected at a depth of 0-50 cm to evaluate the specific area and dry mass of maize roots in different soil layers. Maize grain productivity was also assessed in the three management systems. The results indicated that limestone incorporation significantly increased pH levels and reduced exchangeable aluminum (Al+3) content in deeper soil layers. Surface application of limestone without soil mobilization (SPD) restricted pH increase to the surface layer. However, in the system with minimal mobilization (ESC), limestone particles reacted in deeper layers compared to SPD. Nutrients were more concentrated in the surface layer when applied without incorporation. Maize root distribution also concentrated more in the surface layer for all three management systems, with a reduction as soil depth increased. Therefore, no significant difference in Maize grain productivity was observed among the three soil management systems.